Prospek dan Tantangan Agroedutourism di Moosa Edufarm Kabupaten Solok Provinsi Sumatera Barat - Imam Malik Tarigan; James Hellyward; Budi Rahayu Tanama Putri (Universitas Batanghari Jambi, 2023)
Developing Agroedutourism needs to look at the prospects and challenges ahead. The purpose of this study is to analyze the prospects and challenges of agroedutourism in moosa edufarm solok district of west sumatra province. This research was conducted by field observations and interviews with the management. Further the data obtained are analyzed descriptively. The results of this study are in the management of agroedutourism for cattle farming with adult pen sizes which currently accommodate a maximum of 31.5 heads or 31.5 ST livestock. This still shows prospects in the development of cattle in the future. In terms of the carrying capacity of animal feed forage (KPPTR) Effective, it shows that the increase in cattle population in moosa cannot be done because it is negative (-) 24.14ST based on BK needs. This is because the grass forage land managed independently by Moosa Edufarm is only 0.49 ha while the total real population of ST is 32.25. This will be a challenge going forward for managers. In addition, the challenges in managing agroedutoruism in Moosa Edufarm are the outbreak of diseases that attack humans and cattle, the marketing of wagyu cattle which can only be done to certain groups (middle and upper consumers).